Randomized study of digital single-operator cholangioscope compared to fiberoptic single-operator cholangioscope in a novel cholangioscopy bench model - Shah, Raj J.; Neuhaus, Horst; Parsi, Mansour; Reddy, D. Nageshwar; Pleskow, Douglas K. (Endoscopy International Open, 2018)
Background and study aims Cholangiopancreatoscopy is utilized for diagnosis and therapy of pancreaticobiliary disorders. a fully-disposable, digital, single-operator cholangioscope (DSOC) was developed with high image resolution and wide field-of-view. This bench study compared the new DSOC to the previous semi-disposable, fiber-optic cholangioscope (FSOC) prior to the clinical availability of the DSOC system.Methods Five experts performed one practice run followed by randomized runs comparing DSOC to FSOC in a biliary tract model consisting of three fixed left-intrahepatic tracts (LIHD), and variable common bile duct (CBD) and right-intrahepatic tracts (RIHD) with seven total lesions in multiple configurations. Timed runs aimed to visualize and target each lesion using miniature biopsy forceps. Definitions: visual success, visualizing targets; targeting success, touching target with forceps; complete run, touching seven targets within 20 minutes. Image quality, ease-of-use, and time to completion were recorded.Results Thirty-seven evaluable runs (20 DSOC, 17 FSOC) were completed. DSOC was superior to FSOC in Visual (99 % vs. 67 %, P < 0.001) and targeting success (6.6 vs. 4.5, P = 0.009), proportion of complete runs (13 /20 vs. 0 /17, P < 0.001) and time of run (10.1 min vs. 15.4 min, P < 0.001). For fixed LIHD, DSOC achieved higher targeting success compared to FSOC (2.6 vs. 1.1, P < 0.001) with no difference in RIHD and CBD targets (4.0 vs. 3.4, P = 0.39). Investigators reported superior image quality and ease-of-use with DSOC. Conclusions In this model, DSOC performed superiorly to FSOC in image quality, visualization, and maneuverability. The model could potentially be utilized for training endoscopists less experienced with cholangiopancreatoscopy.